Sistem Operasional Pegadaian Syariah Berdasarkan Surah Al-Baqarah 283 pada PT. Pegadaian (Persero) Cabang Syariah Gunung Sari Balikpapan - Rachmad Saleh Nasution (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
Pawn is one type of agreement debt receivable and Pawnshops is itself a financial institution. To guarantee the existence of an element of trust from the borrower against the debtor, then the party is needed there is stuff in powned as collateral against debts or loans. The goods remain the property of people who pawn, but controlled by the recipient of the goods (the lender). The legitimacy of the practice of this pledge has been around since the days of the Prophet, which is where the Prophet Muhammad himself doing this practice. Islamic pawn shops Gunung Sari Balikpapan is a non-bank financial institutions that provide financing/loan to the community. The goal of this institution is to eradicate dark pawn and loan sharks that requires the borrower to pay interest from the loans, which it is very damning for the people of the small or medium sized down. In this research analyzed the operational system of Islamic pawn shops that applied Shariah Pawnshops Gunung Sari Balikpapan based on surah al-Baqarah 283. source of data used in this study i.e., primary data and secondary data. Primary data obtained through direct observation and interviews, with the results of the data in the form of the documents operational system perum pawn shops and the results of the interviews to relevant parties. While secondary data in the form of literature-literature that discusses Islamic pawn shops, either in the form of books, journals, dissertations, theses and more. Based on the results of the analysis in this study, it can be inferred that Sharia Branch Pawnshops Gunung Sari Balikpapan in carrying out its operational system is in compliance with the provisions of the Shariah, or based on the study of fiqh mu'amalah about pawn. As for pawn shops that contribute products dominant against revenues this pawn shops are sourced from the pawn (rahn) products, which are present around 80% of the total income of Syariah Branches Pawnshops Gunung Sari Balikpapan.